If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t(x) = 6 + 3x + -2 Multiply t * x tx = 6 + 3x + -2 Reorder the terms: tx = 6 + -2 + 3x Combine like terms: 6 + -2 = 4 tx = 4 + 3x Solving tx = 4 + 3x Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Divide each side by 'x'. t = 4x-1 + 3 Simplifying t = 4x-1 + 3 Reorder the terms: t = 3 + 4x-1
| k^2=-2k+24 | | (-5a^2b)(3a^2b^2)=x | | .5*-6=4 | | 5x+12=-11x | | 9-2logx=10 | | 7(1+y)=-3(y+2) | | 27m=135 | | -3m-4=10m | | d(x)=12-0.25x | | 12x=-4x+2 | | 21+4=16 | | 8cosx-2=0 | | 2x+5(4x+19)=205 | | 7+4c=10 | | x+10/4=7 | | -10-4n^2=-330 | | N+3=21 | | h(x)=7-2x | | 4.5m+(-3.2m)-13=-2.63 | | 9x-4(x-3)=712 | | 92=72+4h | | 9m=51 | | 9z=20+16 | | ((2)3.14+(1.125)3.14)= | | 27=9a | | 16-c=18 | | v^2-5=4v | | -9(-10x-25)=1125 | | ax^2-30x+c=0 | | 100x-1x= | | 4(3x-2)+2(3x+1)=2x-54 | | 3x-(-12)=-2x+2 |